2016
DOI: 10.3389/fpls.2016.00580
|View full text |Cite
|
Sign up to set email alerts
|

Moss Pathogenesis-Related-10 Protein Enhances Resistance to Pythium irregulare in Physcomitrella patens and Arabidopsis thaliana

Abstract: Plants respond to pathogen infection by activating signaling pathways leading to the accumulation of proteins with diverse roles in defense. Here, we addressed the functional role of PpPR-10, a pathogenesis-related (PR)-10 gene, of the moss Physcomitrella patens, in response to biotic stress. PpPR-10 belongs to a multigene family and encodes a protein twice the usual size of PR-10 proteins due to the presence of two Bet v1 domains. Moss PR-10 genes are differentially regulated during development and inoculatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 86 publications
0
35
0
Order By: Relevance
“…In P. patens , infection by oomycete and fungal pathogens leads to up-regulation of the usual suspects of angiosperm defense signaling: PAL, Dirigent ( DIR ), Chalcone synthase ( CHS) and Pathogen related ( PR ) genes, as well as genes involved in JA and JA-precursor biosynthesis, such as LOX, AOS and OPR [62,63,137]. This is, however, not surprising, since infections with B. cinerea or two Pythium pathogens lead to OPDA production [62,63].…”
Section: Evolution Of Phytohormone Defense Networkmentioning
confidence: 99%
“…In P. patens , infection by oomycete and fungal pathogens leads to up-regulation of the usual suspects of angiosperm defense signaling: PAL, Dirigent ( DIR ), Chalcone synthase ( CHS) and Pathogen related ( PR ) genes, as well as genes involved in JA and JA-precursor biosynthesis, such as LOX, AOS and OPR [62,63,137]. This is, however, not surprising, since infections with B. cinerea or two Pythium pathogens lead to OPDA production [62,63].…”
Section: Evolution Of Phytohormone Defense Networkmentioning
confidence: 99%
“…It was recently shown that chitin oligosaccharides induce the expression of P. patens chitinase, which inhibits the growth of the fungus Trichoderma viride , suggesting that this enzyme could play a role in moss defense (Kobaru et al, 2016). Moss lines overexpressing PpPR-10 are more resistant to P. irregulare infection and accumulate unknown cell wall polymers, probably reinforcing the cell walls and increasing resistance to pathogens (Castro et al, 2016). PpPR-10 binds cytokinin (Gonneau et al, 2001), however, the biological relevance of this binding capacity in plant defense against pathogens is currently unknown.…”
Section: Moss Defense Genes and Gene Acquisition By Horizontal Transfermentioning
confidence: 99%
“…Causal genes underlying plant QR have been characterized with molecular roles in initial perception of pathogens (NB-LRR and RLK), signal transduction, and downstream defense and host metabolism [38]. As one group of defense components, PR10s have been identi ed in a number of plant species from moss, gymnosperms, to higher angiosperm plants [16]. Differential expression of PR10 genes in responses to biotic and abiotic stressors implied their potential roles in plant immunity systems.…”
Section: Discussionmentioning
confidence: 99%